2002
DOI: 10.1046/j.1083-4389.2002.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐Regulation of Inducible Nitric Oxide Synthase and Nitric Oxide in Helicobacter pylori‐Infected Human Gastric Epithelial Cells: Possible Role of Interferon‐γ in Polarized Nitric Oxide Secretion

Abstract: These results suggest that apical NO production mediated by MAP kinase in H. pylori-infected gastric epithelial cells may influence the bacteria and basolateral production of NO and IL-8 may play a role in the tissue inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
(67 reference statements)
0
36
0
Order By: Relevance
“…However, other in vitro studies demonstrated that H. pylori infection and IFN-␥ act synergistically, for example, to induce apoptosis (29) and increase major histocompatibility complex class II (20) and iNOS (34) expression. One possible explanation for this discrepancy is that in other models IFN-␥ was introduced prior to or simultaneously with bacterial infection (20,34) rather than, as in this study, after a period of infection. Whether the effect of H. pylori infection on IFN-␥-dependent cell functions in vivo is synergistic or inhibitory ultimately may also depend on the balance between STAT1 and non-STAT1 IFN-␥ signaling (23,42) and on the influence of other cytokines, such as tumor necrosis factor alpha and IL-1␤, secreted by immune cells in the gastric mucosa (61).…”
Section: Discussionmentioning
confidence: 43%
“…However, other in vitro studies demonstrated that H. pylori infection and IFN-␥ act synergistically, for example, to induce apoptosis (29) and increase major histocompatibility complex class II (20) and iNOS (34) expression. One possible explanation for this discrepancy is that in other models IFN-␥ was introduced prior to or simultaneously with bacterial infection (20,34) rather than, as in this study, after a period of infection. Whether the effect of H. pylori infection on IFN-␥-dependent cell functions in vivo is synergistic or inhibitory ultimately may also depend on the balance between STAT1 and non-STAT1 IFN-␥ signaling (23,42) and on the influence of other cytokines, such as tumor necrosis factor alpha and IL-1␤, secreted by immune cells in the gastric mucosa (61).…”
Section: Discussionmentioning
confidence: 43%
“…sequestration and production of antibacterial peroxide species during the inflammatory response (36,37). Myeloperoxidase (MPO) and nitric oxide synthase 2 (NOS2) also limit bacterial growth by production of hypochlorous acid and NO, respectively (38)(39)(40). In a whole-genome microarray screen of duodenal biopsy specimens taken from cholera patients, genes for these four proteins consistently displayed the same regulatory patterns (2, 6).…”
Section: Discussionmentioning
confidence: 99%
“…The Caco-2 cell line is a well-characterized model of the gut epithelium and is capable of differentiation and polarization (16), and it releases several inflammatory mediators upon treatment with H. pylori (23). It also provides a suitable and frequently cited method for studying the effects of infectious agents as well as probiotic bacteria (47).…”
Section: Fig 4 Effects Of Probiotics Andmentioning
confidence: 99%